Analisis Efektivitas Iklan pada Media YouTube: Studi Kasus pada Iklan Gojek - Dewi Ratih Nurcahyani; Rifki Renaldi (Research Center and Case Clearing House PPM School of Management, 2023)
The existence of social networks can promote the success of the promotion easily, quickly, and inexpensively. Businesses compete to maximize this digital marketing; one of them is Gojek. Gojek's current digital marketing strategy focuses on video marketing via social media (especially YouTube). Gojek's YouTube ads are more frequent and creative than the competition's. However, the Gojek brand has seen a sharp decline in recent years. Calculate the importance of the effectiveness of advertising for the evaluation. This study looks at the factors that affect the effectiveness of Gojek ads on the YouTube app. Multiple linear regression with SPSS version 23.0 is the measurement tool for this study. The results show that the advertising attractiveness and impression cycles significantly positively affect the three analysis variables. In contrast, the advertising information value variables do not have significant positive effects on the advertising effects. Therefore, Gojek must pay more attention to various attractive factors and advertising frequency to be successful in advertising.